2005
DOI: 10.1093/cercor/bhi061
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuroanatomy of Human Vocalization: An H215O PET Study

Abstract: Vocalization in lower animals is associated with a well-described visceromotor call system centered on the mesencephalic periacqueductal grey matter (PAG), which is itself regulated by paramedian cortical structures. To determine the role this phylogenetically older system plays in human phonation, we contrasted voiced and unvoiced speech using positron emission tomography and then evaluated functional connectivity of regions that significantly differentiated these conditions. Vocalization was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 64 publications
5
110
2
1
Order By: Relevance
“…Like them, this is consistent with them being linked to the cerebello-cerebral cortex circuits (Callan et al, 2007;Callan et al, 2006;Dresel et al, 2005;Loucks et al, 2007;Murphy et al, 1997;Schulz et al, 2005;Spencer and Slocomb, 2007). Further, like dexterity and bipedality, the kinematics of speech production continues to be refined into adolescence and after (Smith and Zelaznik, 2004).…”
Section: Summary Of Vocalization and Internal Modelssupporting
confidence: 61%
“…Like them, this is consistent with them being linked to the cerebello-cerebral cortex circuits (Callan et al, 2007;Callan et al, 2006;Dresel et al, 2005;Loucks et al, 2007;Murphy et al, 1997;Schulz et al, 2005;Spencer and Slocomb, 2007). Further, like dexterity and bipedality, the kinematics of speech production continues to be refined into adolescence and after (Smith and Zelaznik, 2004).…”
Section: Summary Of Vocalization and Internal Modelssupporting
confidence: 61%
“…However, in adults, a PET study found that during voiced speech (which shares some laryngeal control mechanisms with crying), blood flow increased in the PAG, as well as the cerebellar vermis and parts of the thalamus [103]. This study also found activation in cortical regions (see below).…”
Section: The Neural Mechanisms Underlying Cryingmentioning
confidence: 54%
“…However, given the likelihood that similar laryngeal action is involved in both crying and production of voiced sounds in adults, a PET study describing cortical activation during production of voiced speech is of interest. Shulz, et al [103] found significant elevation of regional blood flow in the inferior operculum of the prefrontal gyrus, the medial prefrontal cortex and the anterior cingulate cortex in voiced but not during whispered speech.…”
Section: Forebrain Mechanisms Of Cry Productionmentioning
confidence: 99%
“…Another recent study has further shown a functional coupling between auditory and motor areas during vocalization (31). The premotor and inferior parietal cortices, also involved in speech production, exhibit increased connectivity during speech perception (32).…”
Section: Shifting Of Neural Priming Directionsmentioning
confidence: 88%